2021
DOI: 10.3390/ijms22136720
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterisation of Uterine Endometrial Proteins during Early Stages of Pregnancy in Pigs by MALDI TOF/TOF

Abstract: The molecular mechanism underlying embryonic implantation is vital to understand the correct communications between endometrium and developing conceptus during early stages of pregnancy. This study’s objective was to determine molecular changes in the uterine endometrial proteome during the preimplantation and peri-implantation between 9 days (9D), 12 days (12D), and 16 days (16D) of pregnant Polish Large White (PLW) gilts. 2DE-MALDI-TOF/TOF and ClueGOTM approaches were employed to analyse the biological netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…The most classically used has been the two-dimensional (2D) gel electrophoresis followed by mass spectrometry (MS) or MALDI TOF-TOF analysis to identify protein spots. The 2D-MS/MALDI TOF-TOF has been used to identify 70 to 500 proteins in the peri-implantation period (d 9 to 16) and 820 proteins at mid-pregnancy (d 40 to 93) in the endometrium of pregnant and non-pregnant sows [ 11 13 , 20 , 21 ]. These proteomic studies have provided information on the dynamic physiological protein profile and how it may relate to maternal recognition and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The most classically used has been the two-dimensional (2D) gel electrophoresis followed by mass spectrometry (MS) or MALDI TOF-TOF analysis to identify protein spots. The 2D-MS/MALDI TOF-TOF has been used to identify 70 to 500 proteins in the peri-implantation period (d 9 to 16) and 820 proteins at mid-pregnancy (d 40 to 93) in the endometrium of pregnant and non-pregnant sows [ 11 13 , 20 , 21 ]. These proteomic studies have provided information on the dynamic physiological protein profile and how it may relate to maternal recognition and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Up (Pregnant vs. non-pregnant) [46] Up (day 12 vs. day 9 of pregnant) [45] Up (9D vs. 16D of pregnancy) [47] Annexin A4 ANXA4 promotes trophoblast cell proliferation and invasion.…”
Section: Legumainmentioning
confidence: 99%
“…The pigs also serve as a valuable model to study pregnancy-related protein expression using proteomic approaches and have gained attention in the fields of biomedical and agricultural sciences [ 139 ]. Thus, proteomic approaches provide a better understanding and characterization of proteins involved in molecular and biological processes in pigs [ 47 ]. There are very few studies that describe the proteome profile of the early phase of pregnancy in pigs ( Table 1 ).…”
Section: Proteomics Of Pigs Uterine Milieu To Understand the Mechanis...mentioning
confidence: 99%
“…Recent studies have shown molecular changes in the porcine endometrium during the peri-implantation period and revealed sixteen differentially expressed proteins involved in the recognition and establishment of early gestation in pigs [ 21 ]. It has been hypothesized that CHEM may affect the proteome of the porcine uterus during implantation, and consequently influence the production of many factors essential for the proper course of gestation.…”
Section: Introductionmentioning
confidence: 99%